Sudachitin, polymethoxyflavone from Citrus sudachi, enhances antigen-specific cellular and humoral immune responses in BALB/c mice - Mitani, Mami (J Clin Biochem Nutr, 2019)
Scdachitin is a polymethoxyflavone (5,7,4'-trihydroxy-6,8,3-trimethoxyflavone) that is found in the peel of Citrus sudachi. We examined the effect of sudachitin on immune response in ovalbumin-immunized BALB/c mice. Treatment with sudachitin increased ovalbumin-specific IL-4 and IL-10 productions. In addition, mice that received sudachitin showed higher levels of ovalbumin-specific IgE, IgG1 and IgG l production than did control mice. The antibody response to the thymus-independent antigen 2,4,6-trinitrophenyl Ficoll was not different in the control and sudachitin groups, suggesting that sudachitin does not directly stimulate antibody production. An in vitro study showed that treatment of sudachitin enhanced the ability of antigen presentation in bone marrow-derived dendritic cells. Furthermore, CD11c(+) cells that had been treated with sudachitin showed increased expression of co-stimulatory molecules. The results indicate that sudachitin regulates immune function both in vivo and in vitro.